(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Complication during anaesthesia is inevitable but judicious start, vigilant monitoring, application of pharmacology can prevent or lessen it. Shivering is one of the complications of Subarachnoid block (SAB). To prevent shivering during SAB many techniques had so long been applied. Among them during shivering giving low dose intravenous Pethidine is so far popular in our country. As the drug is not available all the times due to legal restriction & our socioeconomic circumstances, so we studied with another opioid, Nalbuphine and has got an acceptable result which is equipotent and some where better than that of Pethidine. This randomized prospective study conducted in 60 ASA I, II patients, was designed to explore the efficacy and potency of Nalbuphine in comparison to Pethidine for shivering under subaracnoid block. Patient received Nalbuphine 5mg LV or Pethidine25mg after appearance of shivering. Disappearance and recurrence of shivering, as well as haemodynamics were observed at scheduled intervals. Onset of disappearance of shivering was found at 1 minute in Nalbuphine group (N) (p<0.05) and at 3 minutes in Pethidine group (P) (p <0.05). The complete disappearance of shivering took 5 minutes in N group and 20 minutes in P group. Thus Nalbuphine and Pethidine were equally efficacious, but Nalbuphine was more potent with respect to control of shivering and its recurrence. It was concluded that I.V Nalbuphine is qualitatively superior to Pethidine for control shivering. Key words: Shivering in SAB, Nalbuphine, Pethedine Journal of BSA, Vol. 20, No. 2, July 2007 p.66-69